Apostolicity – The question of Continuity and Authority - Alexander Heindel (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
This article was presented as a research paper for the Ecumenical Theology Course at the Ecumenical Institute Bossey in Switzerland. Apostolicity and the relation to the apostles and the early Christians is a big discussed topic in several ecumenical dialogues. First the article analysis the method and context of five different ecumenical dialogue documents. It goes from multilateral Faith and Order documents like “Baptism, Eucharist, Ministry” and “The Church Towards a Common Vision” over the “Porvoo Common Statement” to two Lutheran/Roman-Catholic documents. Then it identifies some characteristic dimensions of apostolicity and brings the results from the dialogues together. A reading of apostolicity as narrative of continuity and authority in relation to god and Jesus Christ occurs through the chapters. Especially in the question of ministry apostolicity plays an important and differentiated role. The article focusses in the end on the episcopal ministry and develops the differentiation of horizontal and vertical apostolic continuity. Apostolicity is described as a gift of god and becomes obviously through gods action in the ordination act. Finally, the article summarises all results, ideas and new approaches.